Identification and verification of IGFBP3 and YTHDC1 as biomarkers associated with immune infiltration and mitophagy in hypertrophic cardiomyopathy - Li, Yao; Zhang, Wei; Dai, Yan; Chen, Keping (Frontiers in Genetics, 2022)
Background: Hypertrophic cardiomyopathy (HCM) is the main cause of sudden cardiac death among young adults, yet its pathogenesis remains vague. N6-methyladenosine (m6A) methylation modification was involved in various cardiovascular diseases such as coronary heart disease and heart failure, although its influence on HCM remains unclear. This study aimed to explore the potential role of m6A in the diagnosis and pathogenesis of HCM. Methods: GSE36961 including 106 HCM and 39 controls was used in the study. The HCM-related m6A regulators were selected using support vector machine recursive feature elimination and random forest algorithm. A significant gene signature was then established using least absolute shrinkage and selection operator and then verified by GSE130036. Subgroup classification of HCM was performed based on the expression of m6A biomarkers. Gene set variation analysis was employed to explore the functional difference between distinct subgroups. Weighted gene co-expression network analysis was used to determine the m6A-related hub module. Single-sample gene set enrichment analysis was conducted to assess the immune and mitophagy features between subgroups. Besides, transfection of recombinant plasmids with targeted genes into H9c2 cells was performed to further verify the function of the significant biomarkers. Results: Significant difference existed in m6A landscape between HCM and control patients, among which IGFBP3 and YTHDC1 were identified as the independent biomarkers of HCM. Highly infiltrated immune cells (MDSC, macrophages, etc.), more enriched immune-related pathways (TNFα signaling via NFκB and IL6-JAK-STAT3 signaling) and cardiac remodeling-associated pathways (epithelial mesenchymal transition, angiogenesis, etc.) were identified in the subgroup with higher IGFBP3. Consistently, overexpression of IGFBP3 in H9c2 cells led to upregulation of extracellular-matrix-related genes (COL1A2, COL3A1 and MMP9) and inflammation-related genes (TNFα and IL6). Besides, higher YTHDC1 expression seemed to be consistent with less-activated mitophagy (PINK1-PRKN mediated mitophagy) and energy metabolism. Further experiments demonstrated that overexpression of YTHDC1 resulted in up-regulation of PINK and PRKN in cardiomyocytes, which are essential genes mediating mitophagy. Conclusion: Two m6A readers (IGFBP3 and YTHDC1) well distinguished HCM and may facilitate clinical diagnosis. IGFBP3 may play a role in the immune-microenvironments and remodeling of cardiac tissues, while YTHDC1 may influence mitophagy and energy metabolism in HCM.